2022
DOI: 10.1002/ece3.9070
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of light and snail herbivory rather than nutrient loading determine early establishment of submerged macrophytes

Abstract: Submerged macrophytes play a key role in maintaining a clear‐water phase and promoting biodiversity in shallow aquatic ecosystems. Since their abundance has declined globally due to anthropogenic activities, it is important to include them in aquatic ecosystem restoration programs. Macrophytes establishment in early spring is crucial for the subsequent growth of other warm‐adapted macrophytes. However, factors affecting this early establishment of submerged macrophytes have not been fully explored yet. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Understanding the responses of submerged macrophytes to environmental factors is essential for their successful restoration. However, previous studies have insufficiently revealed the effects of the interactions between multiple environmental factors [15,[17][18][19][20][21]. In this study, we investigated the interactions and the mechanisms by which light intensity and SOM load affect submerged macrophyte growth.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Understanding the responses of submerged macrophytes to environmental factors is essential for their successful restoration. However, previous studies have insufficiently revealed the effects of the interactions between multiple environmental factors [15,[17][18][19][20][21]. In this study, we investigated the interactions and the mechanisms by which light intensity and SOM load affect submerged macrophyte growth.…”
Section: Discussionmentioning
confidence: 98%
“…Light intensity and sediment organic matter (SOM) load are environmental factors that affect submerged macrophyte growth. Previous studies have established that light intensity is the primary factor that affects submerged macrophyte growth, as well as water depth, turbidity, number of epiphytes, total suspended matter, and chlorophyll concentration, which indirectly affect plant growth and distribution by influencing the light intensity available to the submerged macrophytes [15,[17][18][19]. As in terrestrial plants with root systems, the growth of submerged macrophytes is undoubtedly influenced by the physicochemical properties of the sediment.…”
Section: Introductionmentioning
confidence: 99%